HIV/AIDS knowledge among MSM in Brazil: a challenge for public policies - Mark Drew Crosland Guimarães; Laio Magno; Maria das Graças Braga Ceccato; Raquel Regina de Freitas Magalhães Gomes; Andrea Fachel Leal; Daniela Riva Knauth; Maria Amélia de Sousa Mascena Veras; Inês Dourado; Ana Maria de Brito; Carl Kendall; Ligia Regina Franco Sansigolo Kerr
ABSTRACT Introduction: High level of HIV/AIDS knowledge is required for an effective adoption of preventive strategies. Objective: To assess HIV/AIDS knowledge among men who have sex with men (MSM) in 12 Brazilian cities. Methods: Respondent-Driven Sampling method was used for recruitment. HIV/AIDS knowledge was assessed by Item Response Theory. Difficulty and discrimination parameters were estimated, and the knowledge score was categorized in three levels: high, medium, and low. Logistic regression was used for analysis. Results: Among 4,176 MSM, the proportion of high level of knowledge was 23.7%. The following variables were positively associated with high knowledge (p < 0.05): age 25+ years old, 12+ years of schooling, white skin color, having health insurance, having suffered discrimination due to sexual orientation, having had a syphilis test, and having received educational material in the previous 12 months. Exchanging sex for money was negatively associated. Conclusions: The proportion of only 23.7% of high HIV/AIDS knowledge was low. We should note that the only potential source of knowledge acquisition associated with high level of knowledge was receiving educational materials. Our study indicates the need for expansion of public prevention policies focused on MSM and with more effective communication strategies, including the development of knowledge that involves motivation and abilities for a safer behavior.